2016
DOI: 10.1111/tmi.12728
|View full text |Cite
|
Sign up to set email alerts
|

Retention in care of HIV‐infected pregnant and lactating women starting ART under Option B+ in rural Mozambique

Abstract: Abstractobjective In 2013, Mozambique adopted Option B+, universal lifelong antiretroviral therapy (ART) for all pregnant and lactating women, as national strategy for prevention of mother-to-child transmission of HIV. We analysed retention in care of pregnant and lactating women starting Option B+ in rural northern Mozambique.methods We compared ART outcomes in pregnant ('B+ pregnant'), lactating ('B+ lactating') and non-pregnant non-lactating women of childbearing age starting ART according to clinical and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
(36 reference statements)
5
40
2
Order By: Relevance
“…A recent study from Malawi, using a more stringent definition of retention, found that 77% and 71% of women were retained at 12 and 24 months on ART respectively . In data from Zimbabwe and Mozambique, only 68% and 42% of women were still receiving ART 12 months after ART initiation . A recent systematic review found a pooled estimate of 76% retained at 12 months on ART in African cohorts .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Malawi, using a more stringent definition of retention, found that 77% and 71% of women were retained at 12 and 24 months on ART respectively . In data from Zimbabwe and Mozambique, only 68% and 42% of women were still receiving ART 12 months after ART initiation . A recent systematic review found a pooled estimate of 76% retained at 12 months on ART in African cohorts .…”
Section: Discussionmentioning
confidence: 99%
“…[15] Moreover, mothers who do not suffer from clinical symptoms might not feel a strong need to adhere to health care appointments and daily drug intake. Previous research suggests that mothers who initiated ART for PMTCT are more likely to drop out of care after delivery than women starting ART for their own health [12, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…In Central Mozambique, less than 45% of women were retained at 90 days after ART initiation [7,8]. It was suggested that women with ART initiation under Option B+ were significantly likelier to be lost to follow-up in the first year or have no follow-up after their first visit than those who initiated ART for their own health [9]. These reports suggest poor levels of engagement in care among women under universal ART, raising concerns pertaining to the effectiveness of the strategy, not only in terms of maternal ART outcomes, but also the programme's success in achieving eMTCT HIV targets.…”
Section: Introductionmentioning
confidence: 99%